HOW IS SOCIAL CAPITAL CONVERTED TO BE ECONOMIC CAPITAL? A CASE STUDY FROM PESANTREN’S SOCIO-ECONOMIC PROJECTS - M Falikul Isbah (Institut Agama Islam Negeri Kendari, 2019)
There is an increasing trend among Indonesian Islamic boarding schools or locally called pesantren to address the socio-economic problems of their neighbouring communities. Over the last two decades, many pesantren have articulated that concern through operating Islamic microfinance business or popularly called BMT (Baitul Maal wat Tamwil) and other enterprise forms. However, the majority of those initiatives are not financially developing. Pesantren Sidogiri is among a few of those exhibit business success and relatively significant social benefits to the Pesantren as well as its graduates. Based on fieldwork findings and the employment of social capital theory, this paper argues that the success of Pesantren Sidogiri’s three business hubs (Kopontren Sidogiri, BMT MMU, BMT UGT) is because the Pesantren has successfully mobilised and managed its rich social capital which is embedded in the Pesantren’s social networks. That social networks have constantly been managed and developed through appropriable social organisations and closure of social networks. The former is evident in the Pesantren’s program of Affiliating Madrasah (madrasah ranting) and Teacher-Internship (guru tugas), while the latter in the Alumni Association (himpunan alumni) and the publication of monthly-Bulletin Sidogiri. These two streams have intentionally or unintentionally provided the Pesantren with a ready-use of social capital to be converted as economic capital in its economic projects.There is an increasing trend among Indonesian Islamic boarding schools or locally called pesantren to address the socio-economic problems of their neighbouring communities. Over the last two decades, many pesantren have articulated that concern through operating Islamic microfinance business or popularly called BMT (Baitul Maal wat Tamwil) and other enterprise forms. However, the majority of those initiatives are not financially developing. Pesantren Sidogiri is among a few of those exhibit business success and relatively significant social benefits to the Pesantren as well as its graduates. Based on fieldwork findings and the employment of social capital theory, this paper argues that the success of Pesantren Sidogiri’s three business hubs (Kopontren Sidogiri, BMT MMU, BMT UGT) is because the Pesantren has successfully mobilised and managed its rich social capital which is embedded in the Pesantren’s social networks. That social networks have constantly been managed and developed through appropriable social organisations and closure of social networks. The former is evident in the Pesantren’s program of Affiliating Madrasah (madrasah ranting) and Teacher-Internship (guru tugas), while the latter in the Alumni Association (himpunan alumni) and the publication of monthly-Bulletin Sidogiri. These two streams have intentionally or unintentionally provided the Pesantren with a ready-use of social capital to be converted as economic capital in its economic projects.